Stigmatised health topics in sport: An action research approach to enhance knowledge and communication - Höök, M.; Knight, C. J.; McGawley, K. (Journal of Sports Sciences, 2026)
Performance development among adolescent athletes is influenced by various factors besides physical training and recovery, such as mental health, energy availability and hormonal symptoms and dysfunction. Despite the frequency with which these health-related challenges occur in athletes, they are often stigmatised topics of discussion. The current study aimed to design, implement, and evaluate an educational intervention to foster knowledge-sharing and communication about stigmatised health topics among late adolescent athletes (i.e. 16-19 years old) and their coaches. An action research methodology was adopted. Twenty-one athletes (12 female, nine male) and four coaches (two female, two male) engaged in two initial group sessions to develop the educational intervention (the planning phase). The planned intervention comprised a series of workshops exploring 1. relative energy deficiency in sport (REDs), low energy availability (LEA) and eating disorders (EDs), 2. mental health (MH) and 3. female and male sex hormone function. Evaluation utilised pre- and post-questionnaires and small group discussions. The intervention facilitated communication between the athletes and coaches by enhancing knowledge through integrated knowledge delivery and shared experiences. However, despite completing this educational intervention, the athletes continued to find communication about their body weight, EDs, and male hormone function challenging, which needs further evaluation.